Association Between Dietary Inflammatory Index and Triglyceride Glucose-Body Mass Index with Iron Deficiency in Reproductive Age Women: Evidence from NHANES 2005-2018 - Ding J; Xu Z; Liang R; Xie S (International Journal of Women's Health)
Jia Ding,1,* Zhehao Xu,2,* Ruiyun Liang,3 Shuangfeng Xie1 1Department of Hematopathology, Sun Yat-sen Memorial Hospital, Sun Yat-sen University, Guangzhou, People’s Republic of China; 2Department of General Medicine, Sun Yat-sen Memorial Hospital, Sun Yat-sen University, Guangzhou, People’s Republic of China; 3Department of Respiratory Medicine, Sun Yat-sen Memorial Hospital, Sun Yat-sen University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shuangfeng Xie, Email xiesf@163.comBackground & Aims: There is a growing focus on the role of dietary factors and metabolic conditions in the evolution and progression of iron deficiency (ID), yet few studies have examined the underlying mechanisms. Dietary Inflammatory Index (DII) is a metric that gauges the inflammatory potential of an overall diet. This study explores the association between DII and triglyceride glucose-body mass index (TyG-BMI) with ID in reproductive-age women.Methods: This analysis utilized data from 2311 reproductive-age women in the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. ID was identified using serum ferritin and transferrin receptor (TfR). The association between DII, TyG-BMI and ID was assessed using weighted logistic regression, linear regression and restricted cubic spline (RCS) models, with receiver operating characteristic (ROC) curve analysis for diagnostic power. Mediation effects of TyG-BMI were further explored by causal mediation analysis.Results: Among reproductive-age women, both DII and TyG-BMI were significantly positively associated with ID (DII: OR = 1.32, 95% CI 1.19, 1.48; TyG-BMI: OR = 1.13, 95% CI 1.02, 1.35). There is a close relationship between the DII index and TfR (β= 1.17, 95% CI 1.03, 1.13). RCS analysis indicated that the relationships were mostly linear (P-overall < 0.05, P-nonlinear > 0.05). Furthermore, TyG-BMI mediated 5.19%, 12.83%, and 5.63% of the associations between DII and ID, Ferritin, and transferrin receptor (TfR), respectively.Conclusion: The findings suggest that targeted interventions to enhance dietary practices, nutritional intake, and overall metabolic well-being may result in substantial amelioration of ID among reproductive women.Keywords: iron deficiency, reproductive women, dietary inflammatory index, triglyceride glucose-body mass index, insulin resistance